Structure factors dictate the ionic conductivity and chemical stability for cubic garnet-based solid-state electrolyte - Shi, Jingyu; Wu, Xiaofeng; Chen, Yutong; Zhang, Yi; Hou, Xiangyan; Lv, Ruike; Liu, Junwei; Jiang, Mengpei; Huang, Keke; Feng, Shouhua (Chinese chemical letters, 2025)
Solid-state electrolytes (SSEs), as the core component within the next generation of key energy storage technologies - solid-state lithium batteries (SSLBs) - are significantly leading the development of future energy storage systems. Among the numerous types of SSEs, inorganic oxide garnet-structured superionic conductors Li7La3Zr2O12 (LLZO) crystallized with the cubic Ia3¯d space group have received considerable attention owing to their highly advantageous intrinsic properties encompassing reasonable lithium-ion conductivity, wide electrochemical voltage window, high shear modulus, and excellent chemical stability with electrodes. However, no SSEs possess all the properties necessary for SSLBs, thus both the ionic conductivity at room temperature and stability in ambient air regarding cubic garnet-based electrolytes are still subject to further improvement. Hence, this review comprehensively covers the nine key structural factors affecting the ion conductivity of garnet-based electrolytes comprising Li concentration, Li vacancy concentration, Li carrier concentration and mobility, Li occupancy at available sites, lattice constant, triangle bottleneck size, oxygen vacancy defects, and Li-O bonding interactions. Furthermore, the general illustration of structures and fundamental features being crucial to chemical stability is examined, including Li concentration, Li-site occupation behavior, and Li-O bonding interactions. Insights into the composition-structure-property relations among cubic garnet-based oxide ionic conductors from the perspective of their crystal structures, revealing the potential compatibility conflicts between ionic transportation and chemical stability resulting from Li-O bonding interactions. We believe that this review will lay the foundation for future reasonable structural design of oxide-based or even other types of superionic conductors, thus assisting in promoting the rapid development of alternative green and sustainable technologies. Insights into the critical impact of structural factors on ionic conductivity and chemical stability for inorganic oxide garnet-based ionic conductors, revealing potential underlying compatibility conflicts between these two properties. [Display omitted]